ANALISIS PERBANDINGAN SEJARAH PERKEMBANGAN BIMBINGAN DAN KONSELING DI AMERIKA SERIKAT DAN INDONESIA - Khasanah, Nurul; Edward, Lucyana Lucky; Rahmah, Aulia Ziyadatur; Ilmi, Dina Nurul; Ekasari, Surya Pandewa (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2025)
Abstract: This research examines the historical development of Guidance and Counseling (BK) in the United States and Indonesia using a descriptive qualitative research approach based on literature studies. Guidance and counseling has an essential role in solving problems in education and individual development. However, each country has a different development journey, which can be influenced by their social context, culture, and needs. In the United States, the development of Guidance and Counseling (BK) began in the early 20th century, with an emphasis on career guidance and mental health. Important figures such as Jesse B. Davis and Frank Parsons played a major role in this development. The institutionalization process of BK was further strengthened by the establishment of the National Vocational Guidance Association (NVGA) and the standardization of counselor training conducted by the Council for Accreditation of Counseling and Related Educational Programs (CACREP). Meanwhile, in Indonesia, counseling has its roots in the struggle for national education, with figures such as K.H. Dewantara. BK was officially included in the education system through the 1975 Curriculum and continues to evolve with an emphasis on the values of Pancasila. Despite their different histories, both countries emphasize the importance of counseling in supporting individual and societal development. This understanding can enrich BK policies and practices that are more adaptive to educational needs. Keywords: Guidance and Counseling; BK History; BK Development; America; Indonesia. Abstrak: Penelitian ini mengkaji tentang perkembangan sejarah perkembangan Bimbingan dan Konseling (BK) di Amerika Serikat dan Indonesia dengan menggunakan pendekatan penelitian kualitatif deskriptif yang berbasis studi literatur. Bimbingan dan konseling memiliki peranan yang esensial dalam memecahkan masalah di dunia pendidikan serta pengembangan individu. Namun, setiap negara memiliki perjalanan perkembangan yang berbeda-beda, bisa dipengaruhi oleh konteks sosial, budaya, dan kebutuhan masing-masing. Di Amerika Serikat, perkembangan Bimbingan dan Konseling (BK) dimulai pada awal abad ke-20, dengan penekanan pada bimbingan karir dan kesehatan mental. Tokoh-tokoh penting seperti Jesse B. Davis dan Frank Parsons berperan besar dalam perkembangan tersebut. Proses institusionalisasi BK semakin diperkuat dengan pendirian National Vocational Guidance Association (NVGA) serta standarisasi pelatihan konselor yang dilakukan oleh Council for Accreditation of Counseling and Related Educational Programs (CACREP). Sementara itu, di Indonesia, BK berakar dari perjuangan pendidikan nasional, dengan tokoh seperti K.H. Dewantara. BK resmi masuk dalam sistem pendidikan melalui Kurikulum 1975 dan terus berkembang dengan penekanan pada nilai-nilai Pancasila. Meskipun memiliki sejarah berbeda, kedua negara menekankan pentingnya BK dalam mendukung perkembangan individu dan masyarakat. Pemahaman ini dapat memperkaya kebijakan dan praktik BK yang lebih adaptif terhadap kebutuhan pendidikan. Kata Kunci: Bimbingan dan Konseling; Sejarah BK; Perkembangan BK; Amerika; Indonesia.